Potential and possibility of extending the campaign to increase VVER-1000 power units on sliding distribution of the secondary circuit - A. S. Grachev; A. A. Lapkis; A. Yu. Smolin (Глобальная ядерная безопасность)
The paper considers the efficiency and possibility of implementing into the operational practice of VVER-1000 power units the campaign extension mode at the sliding pressure of the second circuit. The history of research of Russian nuclear scientists in terms of extending the campaign of VVER reactors is considered. It is shown that reducing the pressure of fresh steam within the permissible limits will release additional reactivity due to the release of the temperature effect and generate additional energy during the operation of the unit on the power effect. A mathematical model of changes in the main parameters of the reactor plant has been compiled, including the reactivity balance equations, the Stodola-Flugel equation for the turbine, the equations of thermal balance and heat transfer in the steam generator. The calculation of the expected increase in electricity generation for modern fuel loads of VVER-1000 reactors has been performed. The degree of compliance of the proposed regime with the current technological limitations of the VVER-1000 «large series» power unit is analyzed. The results of the analysis were confirmed by numerical experiment on a multifunctional mode analyzer of the VVER-1000 reactor unit developed by the MEPhI Research Institute, built on the basis of the ENIKAD medium and the certified diffusion neutron-physical code PROSTOR. Conclusions are drawn about the possibility of introducing the proposed regime into the operational practice of modern VVER-1000 power units.